For x > 1 , show that if S 0 ( x ) = n = 1 ∑ ∞ x n − 1 1 and for ( 1 ≤ l ≤ k ) , S l ( x ) = n = 1 ∑ ∞ x n n l , then S k + 1 ( x ) = n = 1 ∑ ∞ x n n k + 1 = l = 0 ∑ k − 1 ( l k ) S l ( x ) S k − l ( x ) + x 1 S k ( x ) S 0 ( x ) Using the above, if ∫ m + 1 m + 2 n = 1 ∑ ∞ x n n 4 d x = m 4 ( m + 1 ) 4 m 8 + 4 m 7 + 2 1 m 6 + 9 9 m 5 + 2 3 1 m 4 + 2 5 9 m 3 + 1 4 1 m 2 + 4 4 m + 6 for x > 1 and m > 0 , find the value of m to seven decimal places.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Using a method different from that suggested. Let S 0 ( x ) = n = 0 ∑ ∞ x n 1 and S k ( x ) = n = 0 ∑ ∞ x n n k = n = 1 ∑ ∞ x n n k for k ≥ 1 for x > 1 . Then we have:
S k ( x ) ⟹ x S k ( x ) ⟹ S k ( x ) = n = 0 ∑ ∞ x n n k = n = 1 ∑ ∞ x n n k = n = 0 ∑ ∞ x n + 1 ( n + 1 ) k = x 1 n = 0 ∑ ∞ x n ∑ j = 0 k ( j k ) n j = x 1 j = 0 ∑ k ( j k ) n = 0 ∑ ∞ x n n j = x 1 j = 0 ∑ k ( j k ) S j ( x ) = j = 0 ∑ k ( j k ) S j ( x ) = S k ( x ) + j = 0 ∑ k − 1 ( j k ) S j ( x ) = x − 1 1 j = 0 ∑ k − 1 ( j k ) S j ( x )
Now, we have:
S 0 S 1 S 2 S 3 S 4 = n = 0 ∑ ∞ x n 1 = x − 1 x = n = 0 ∑ ∞ x n n = x − 1 1 × x − 1 x = ( x − 1 ) 2 x = n = 0 ∑ ∞ x n n 2 = x − 1 1 ( x − 1 x + ( x − 1 ) 2 2 x ) = ( x − 1 ) 3 x 2 + x = n = 0 ∑ ∞ x n n 3 = x − 1 1 ( x − 1 x + ( x − 1 ) 2 2 x + ( x − 1 ) 3 3 ( x 2 + x ) ) = ( x − 1 ) 4 x 3 + 4 x 2 + x = n = 0 ∑ ∞ x n n 4 = x − 1 1 ( x − 1 x + ( x − 1 ) 2 4 x + ( x − 1 ) 3 6 ( x 2 + x ) + ( x − 1 ) 4 4 ( x 3 + 4 x 2 + x ) ) = ( x − 1 ) 5 x 4 + 1 1 x 3 + 1 1 x 2 + x
Therefore, we have:
I = ∫ m + 1 m + 2 n = 0 ∑ ∞ x n n 4 d x = ∫ m + 1 m + 2 ( x − 1 ) 5 x 4 + 1 1 x 3 + 1 1 x 2 + x d x Let u = x − 1 ⟹ x = u + 1 , d u = d x = ∫ m m + 1 u 5 u 4 + 1 5 u 3 + 5 0 u 2 + 6 0 u d u = ∫ m m + 1 ( u 1 + u 2 1 5 + u 3 5 0 + u 4 6 0 + u 5 2 4 ) d u = ln u − u 1 5 − u 2 2 5 − u 3 2 0 − u 4 6 ∣ ∣ ∣ ∣ m m + 1 = ln ( m m + 1 ) − ( m + 1 ) 4 1 5 ( m + 1 ) 3 + 2 5 ( m + 1 ) 2 + 2 0 ( m + 1 ) + 6 + m 4 1 5 m 3 + 2 5 m 2 + 2 0 m + 6 = ln ( m m + 1 ) + m 4 ( m + 1 ) 4 1 5 m 6 + 9 5 m 5 + 2 3 0 m 4 + 2 5 9 m 3 + 1 4 1 x 2 + 4 4 m + 6 = ln ( m m + 1 ) + m 4 ( m + 1 ) 4 x 8 + 4 m 7 + 2 1 m 6 + 9 9 m 5 + 2 3 1 m 4 + 2 5 9 m 3 + 1 4 1 x 2 + 4 4 m + 6 − m 4 ( m + 1 ) 4 x 8 + 4 m 7 + 6 m 6 + 4 m 5 + 1 m 4 = ln ( m m + 1 ) + m 4 ( m + 1 ) 4 x 8 + 4 m 7 + 2 1 m 6 + 9 9 m 5 + 2 3 1 m 4 + 2 5 9 m 3 + 1 4 1 x 2 + 4 4 m + 6 − 1
This implies that:
ln ( m m + 1 ) m m + 1 ⟹ m = 1 = e = e − 1 1 ≈ 0 . 5 8 1 9 7 6 7
Problem Loading...
Note Loading...
Set Loading...
Let x > 1 .
To Show: If S 0 ( x ) = ∑ n = 1 ∞ x n − 1 1 and for ( 1 ≤ l ≤ k ) S l ( x ) = ∑ n = 1 ∞ x n n l , then
S k + 1 ( x ) = ∑ n = 1 ∞ x n n k + 1 = ( ∑ l = 0 k − 1 ⎝ ⎛ k l ⎠ ⎞ S l ( x ) S k − l ( x ) ) + x 1 S k ( x ) S 0 ( x ) .
Let x > 1 .
S k + 1 = ∑ n = 1 ∞ x n n k + 1 = ∑ j = 1 ∞ ∑ n = j ∞ x n n k = ∑ j = 1 ∞ ∑ n = 0 ∞ x j + n ( j + n ) k =
∑ j = 1 ∞ ( x j j k ∑ n = 1 ∞ x n − 1 1 + ⎝ ⎛ k 1 ⎠ ⎞ x j j k − 1 ∑ n = 1 ∞ x n n + ⎝ ⎛ k 2 ⎠ ⎞ x j j k − 2 ∑ n = 1 ∞ x n n 2 + . . . + ⎝ ⎛ k l ⎠ ⎞ x j j k − l ∑ n = 1 ∞ x n n l + . . . + x j 1 ∑ n = 1 ∞ x n n k ) .
Letting S 0 ( x ) = ∑ n = 1 ∞ x n − 1 1 and for ( 1 ≤ l ≤ k ) S l ( x ) = ∑ n = 1 ∞ x n n l ⟹
S k + 1 = S 0 ( x ) S k ( x ) + ⎝ ⎛ k 1 ⎠ ⎞ S 1 ( x ) S k − 1 ( x ) + ⎝ ⎛ k 2 ⎠ ⎞ S 2 ( x ) S k − 2 ( x ) + . . . + ⎝ ⎛ k l ⎠ ⎞ S l ( x ) S k − l ( x ) = . . . +
x 1 S k ( x ) S 0 ( x ) = ∑ n = 1 ∞ x n n k + 1 = ( ∑ l = 0 k − 1 ⎝ ⎛ k l ⎠ ⎞ S l ( x ) S k − l ( x ) ) + x 1 S k ( x ) S 0 ( x ) .
From the summation it should be clear that S 1 ( x ) = ∑ n = 1 ∞ x n − 1 n = x 1 ( S 0 ( x ) ) 2 .
Using the above:
Let x > 1 .
Clearly the geometric series S 0 = ∑ n = 1 ∞ x n − 1 1 = x − 1 x
For k = 0 : S 1 ( x ) = ∑ n = 1 ∞ x n − 1 n = x 1 ( S 0 ( x ) ) 2 = x 1 ( x − 1 x ) 2 = ( x − 1 ) 2 x .
For k = 1 : S 2 ( x ) = ∑ n = 1 ∞ x n n 2 = S 0 ( x ) S 1 ( x ) + x 1 S 1 ( x ) S 0 ( x ) = ( x − 1 ) 3 x 2 + x
For k = 2 : S 3 ( x ) = ∑ n = 1 ∞ x n n 3 = S 0 ( x ) S 2 ( x ) + 2 ( S 1 ( x ) ) 2 + x 1 S 1 ( x ) S 0 ( x ) = ( x − 1 ) 4 x 3 + 4 x 2 + x
For k = 3 : S 4 ( x ) = ∑ n = 1 ∞ x n n 4 = S 0 ( x ) S 3 ( x ) + 3 S 1 ( x ) S 2 ( x ) + 3 S 2 ( x ) S 1 ( x ) + x 1 S 3 ( x ) S 0 ( x ) = ( x − 1 ) 5 x 4 + 1 1 x 3 + 1 1 x 2 + x
Let u = x − 1 ⟹ d x = d u ⟹ ∫ m + 1 m + 2 S 4 ( x ) d x = ∫ m m + 1 u 5 u 4 + 1 5 u 3 + 5 0 u 2 + 6 0 u + 2 4 d u = ∫ m m + 1 u 1 + 1 5 u − 2 + 5 0 u − 3 + 6 0 u − 4 + 2 4 u − 5 d u = ( ln ( u ) − u 1 5 − u 2 2 5 − u 3 2 0 − u 4 6 ) ∣ m m + 1 =
ln ( m m + 1 ) + m 4 ( m + 1 ) 4 1 5 m 6 + 9 5 m 5 + 2 3 0 m 4 + 2 5 9 m 3 + 1 4 1 m 2 + 4 4 m + 6 = m 4 ( m + 1 ) 4 m 8 + 4 m 7 + 2 1 m 6 + 9 9 m 5 + 2 3 1 m 4 + 2 5 9 m 3 + 1 4 1 m 2 + 4 4 m + 6 = m 4 ( m + 1 ) 4 m 8 + 4 m 7 + 6 m 6 + 4 m 5 + m 4 + 1 5 m 6 + 9 5 m 5 + 2 3 0 m 4 + 2 5 9 m 3 + 1 4 1 m 2 + 4 4 m + 6 = 1 + m 4 ( m + 1 ) 4 1 5 m 6 + 9 5 m 5 + 2 3 0 m 4 + 2 5 9 m 3 + 1 4 1 m 2 + 4 4 m + 6 ⟹ ln ( m m + 1 ) = 1 ⟹ m m + 1 = e ⟹ m = e − 1 1 = 0 . 5 8 1 9 7 6 7 .